TO IMPROVE STUDENTS’ INTERPERSONAL COMMUNICATION SKILLS BY MEANS OF COOPERATIVE LEARNING IOC AT PIBA PROGRAM OF UIN ALAUDDIN MAKASSAR - Syarif Hidayat Nasir (Universitas Islam Negeri Alauddin Makassar, 2015)
This study was a CAR situated at the second semester students of Foreign Language Intensive Program (PIBA) of UIN Alauddin Makassar. The students experienced crusial problems in Interpersonal Conversation. They seemed likely afraid to talk as well as to speak something in front of the class. Moreover, they considered spoken English such a hell subject. Consequently, the study employed a kind of Cooperative Learning named Inside Outside Circle in the learning process to introduce better English conversation to students. Finally, it was found that there was a significant achievement as well as a marvelous performance gained by students from the first up to the second cycle. The mean score at pre cycle test was only 15, 45. Then, It raised up to 46, 80 at the first cycle as well as 70,20 at the second cycle. Furthermore, the highest score of pre-test was 37 and changed to 80,71 in the first cycle post test, then raised up to 89,12 in the second cycle. Otherwise, the lowest score is 1 becomes 18 in the first cycle and 60 in the second cycle. Thus,the Cooperative Learning model IOC could increase the students’ capability of conducting better English Interpersonal Conversation as well as encourage students’ class involvement.